Differential Search Algorithm for Reliability Enhancement of Radial Distribution System. Issue 1 (2nd January 2016) - Ray, Saheli; Bhattacharya, Aniruddha; Bhattacharjee, Subhadeep
Abstract: This article proposes a differential search algorithm to solve a distribution system reliability optimization problem. Optimum failure rate and repair time of different distributor segments of a distribution network have been calculated to enhance reliability of radial distribution system, both without distributed generation and incorporating distributed generation as standby unit. The differential search algorithm, a recently developed optimization algorithm having improved exploration and exploitation ability, has been implemented to solve the reliability optimization problem in search for superior quality solution. The differential search algorithm mimics the Brownian-like random-walk movement used by an organism for its migration. Simulation results establish that the proposed approach outperforms other existing optimization techniques in terms of quality of solution obtained and computational efficiency as applied to optimize failure rate and repair time of a radial distribution network.